The Antimicrobial Peptide LL-37 as a Possible Adjunct for the Proliferation and Differentiation of Dental Pulp Stem Cells - Milhan, Noala Vicensoto Moreira [UNESP] (2017)
Introduction This study evaluated the biocompatibility of 5 and 10 μg/mL LL-37 in vitro and its effect on the differentiation of human dental pulp stem cells (DPSCs) into odontoblast-like cells. Methods Cell viability, genotoxicity, nitric oxide production, cell cycle, dentine sialophosphoprotein (DSPP) production, and DSPP gene expression. Results Concentrations of 5 and 10 μg/mL of LL-37 were not cytotoxic and generally increased cell viability, especially on the third day (P <.05). The tested concentrations did not induce genotoxicity (P <.05). LL-37 did not significantly alter nitrite production at either concentration. Cell cycle analysis revealed that 10 μg/mL of LL-37 arrested cells in G0/G1 (P <.05). The control group exhibited higher numbers of cells in other phases of the cell cycle (P <.05). The expression of the DSPP protein and gene was also higher in the 10 μg/mL of LL-37 group (P <.05). Conclusions These results demonstrated that LL-37 was biocompatible at these concentrations and increased the number of viable cells, especially during the initial period. The 10 μg/mL concentration arrested the cell cycle and increased expression of the DSPP protein and gene, which indicates that this peptide contributes to odontoblastic differentiation.